Possibilities for growing kenaf (Hibiscus cannabinus L) in Argentina as biomass feedstock under dry-subhumid and semiarid climate conditions - Falasca, Silvia Liliana (2014)
Kenaf (Hibiscus cannabinus L.) is an annual herbaceous crop with a high biomass production. In this paper, and based on international bibliography, the authors outline an agro-climatic and agro-ecological zoning model to determine potential growing areas in Argentina for kenaf. The bioclimatic variables considered were: 150 frost-free days, isohyets of 500, 780 and 1200 mm corresponding to November–March (the growing period), a mean annual temperature of 11.5 °C and temperatures of 15 °C, 20 °C, 25 °C and 27 °C during the growing period. The agroclimatic indices, which determine different classes of suitability, were integrated in a Geographic Information System in order to create thermic and hydric regions. The maps were superimposed, and the overlapping regions delineated the agroclimatic zoning. Thornthwaite's Moisture Index = 0 was overlapped on the agroclimatic zoning map to guarantee that the lands to be occupied by the proposed energy crop would be located under dry-subhumid, semiarid or arid climate conditions. This last map was superimposed on another one that determined unsuitable soils for traditional agriculture. The overlapping regions defined the agro-ecological zoning for kenaf. This is an innovative work, made by the implementation of a geographic information system that can be updated by the further incorporation of complementary information, with the consequent improvement of the original database. Furthermore, its focus is not merely local since the model described may be applied to any part of the world, using the agroclimatic limits presented in this paper.